2021
DOI: 10.1097/eja.0000000000001531
|View full text |Cite
|
Sign up to set email alerts
|

Posteromedial quadratus lumborum block versus wound infiltration after caesarean section

Abstract: BACKGROUND Reducing pain and minimising the use of opioids after caesarean section are crucial to enhancing maternal recovery and promoting mother-newborn interaction. Various techniques have been implemented to improve analgesia. We compared the analgesic efficacy of posteromedial quadratus lumborum block with that of wound infiltration following elective caesarean section. OBJECTIVE We hypothesised that within a multimodal analgesia approach, posterom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Third, we did not administer intrathecal opioids after CD to avoid interfering with the interfascial plane blocks. The issue of whether the addition of QLB to parturients receiving neuraxial morphine results in additional analgesic benefit compared with neuraxial morphine alone is still a point of discussion in meta-analyses and clinical studies [22,32,33]. Fourth, all parturients in the current study received the Joel-Cohen incision, but not Pfannenstiel incision.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Third, we did not administer intrathecal opioids after CD to avoid interfering with the interfascial plane blocks. The issue of whether the addition of QLB to parturients receiving neuraxial morphine results in additional analgesic benefit compared with neuraxial morphine alone is still a point of discussion in meta-analyses and clinical studies [22,32,33]. Fourth, all parturients in the current study received the Joel-Cohen incision, but not Pfannenstiel incision.…”
Section: Discussionmentioning
confidence: 92%
“…The pain experienced after CD is complex and consists of somatic pain originating from the abdominal wall incision located in the cutaneous segment area innervated by the anterior branch of the T12~L1 spinal nerves and the rectus abdominis dissected in the surgical area innervated by the anterior branches of the T6~T7 thoracic nerves [22]. The pain also has a visceral component due to uterine exteriorization and stretching innervated by the T5~T10 thoracic sympathetic nerve [23].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the QLB for postoperative analgesia after CS has been studied utilizing spinal anesthesia with and without intrathecal morphine. Without intrathecal morphine, many studies have demonstrated the effectiveness of the QLB to decrease the pain scores and decrease the total dose of postoperative rescue analgesic compared to sham procedure (12)(13)(14)(15) , TAP block (16)(17)(18) , or wound infiltration (19) .…”
Section: Discussionmentioning
confidence: 99%
“…The original lateral approach (QLB-I) (23) is now not used after CS. (12) Most of the current studies have utilized the posterior approach (QLB-II) (12,13,(15)(16)(17)(19)(20)(21)(22) , however, other studies have successfully utilized the transmuscular approach (QLB-III) (14,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Koncept multimodalne analgezije vključuje načrtno kombiniranje področnih tehnik lajšanja bolečine s sistemskimi analgetiki, različne farmakodinamične in farmakokinetične lastnosti z namenom doseganja sinergističnih analgetičnih učinkov (Holland et al, 2019;Smith, Young, Blosser, & Poole, 2019: Bornstein et al, 2021. Z multimodalnimi režimi analgezije lahko po carskem rezu pomembno zmanjšamo uporabo opioidnih analgetikov, ob tem pa še vedno zagotovimo ustrezno obvladovanje bolečine (Stopar-Pintarič et al, 2021;Višić, Stopar Pintarič, Albreht, Blajić, & Lučovnik, 2021).…”
Section: Uvodunclassified